Peran Mahasiswa Indonesia di Luar Negeri dalam Melestarikan Budaya dan Menguatkan Identitas Nasional - Elizabeth Benedycta Eqzaputri; Faiz Halwa Diafreza; Kezia Lilienasanti Pariyanto; Sorya Hastriningrum Denty Purwadi; Winanti Wahyu Pratiwi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
In the current era of globalization, ease of access to information and the expansion of scholarship opportunities have facilitated greater mobility among Indonesian students seeking higher education abroad. This phenomenon has contributed to the rise of Indonesian intellectual diasporas, who, while pursuing academic excellence, also serve as cultural ambassadors representing Indonesia on the global stage. Their presence abroad extends beyond academic engagement, encompassing efforts to promote national identity and foster cultural understanding. This study examines the dual role of Indonesian students overseas, focusing on their pursuit of education as well as their contributions to the preservation and promotion of Indonesian cultural identity in international contexts. Expressions of patriotism are frequently demonstrated through the performance and dissemination of traditional arts and cultural practices. By doing so, these students not only maintain a connection to their homeland but also enhance Indonesia’s cultural visibility in diverse academic and social environments.